Taxonomic review of the Palaearctic species of the Cheilosia caerulescens-group (Diptera, Syrphidae) - Ståhls, Gunilla (Zookeys, 2017)
Abstract. The Palaearctic species of the Cheilosia caerulescens group (Diptera: Syrphidae) are revised in this work. The species group belongs to the genus Cheilosia subgenus Taeniocheilosia Oldenberg. One new species is described from north Caucasus, Cheilosia (Taeniocheilosia) circassica sp. n. Cheilosia primulae Hering is established as a junior synonym of Cheilosia laeviventris Loew. Four lectotype designations are made. The species of the Cheilosia caerulescens group are redescribed and illustrated, and a table of diagnostic characters and an identification key to species are provided. MtDNA COI barcodes were generated for several specimens of C. (T.) caerulescens Meigen and other Cheilosia (Taeniocheilosia) and Cheilosia s. str. taxa. Parsimony and maximum likelihood analyses did not place the morphologically similar C. hercyniae Loew in the C. caerulescens group but among other Cheilosia (Taeniocheilosia) taxa. The following eight taxa are included in the Cheilosia (T.) caerulescens group of species: Cheilosia armeniaca Stackelberg, 1960, C. caerulescens caerulescens (Meigen, 1822), C. caerulescens calculosa Skufjin, 1977, C. circassica sp. n., C. herculana Brădescu, 1982, C. kerteszi Szilády, 1938, C. laeviventris Loew, 1857, and C. venosa Loew, 1857.